An exploratory study of visual and psychological correlates of preference for onscreen subpixel-rendered text - Bias, Randolph G.; Larson, Kevin; Huang, Sheng-Cheng; Aumer-Ryan, Paul R.; Montesclaros, Chris (Journal of the Association for Information Science and Technology, 2010)
Font-rendering technologies play a critical role in presenting clear and aesthetic fonts to enhance the experience of reading from computer screens. This article presents three studies investigating visual and psychological correlates of people's preferences toward different onscreen text enhancements such as ClearType developed by Microsoft. Findings suggested that (a) people's acuity and hue sensitivity were two major factors that affect their preferences to ClearType's color filtering of subpixels on fonts, and (b) specific personality traits such as disagreeableness also could correlate with people's impressions of different onscreen text enhancements that were used. These empirical data would inform digital typographers and human–computer interaction scientists who aim to develop better systems of onscreen reading. © 2010 Wiley Periodicals, Inc.